Diseño de un Sistema de Gestión Ambiental (SGA), basado en la norma ISO 14001 2015, para la Planta de beneficio Alto Vizcaya ubicado en la Parroquia Malvas, cantón Zaruma, provincia de El Oro - Cuenca Gonzabay,Michael Bladimir (2018)
Abstract:The Alto Vizcaya beneficiation plant is dedicated to the extraction and processing of auriferous minerals, which is why all types of activities that are negative to the means of transport, affect the remote settlers and their workers. For this reason, an environmental management system SGA is designed for the plant, based on the ISO 14001: 2015 standard, which allows controlling its environmental impacts and reducing, improving its image and competitiveness against other mining companies in the country. To this end, the initial environmental review of the beneficiation plant was carried out, which recognized 11 processes and 39 activities in its structure, one more than the identification of more than 130 impacts with an importance ranging from low to moderate. In this way, the environmental management system is structured in 12 procedures, ranging from the scope definition of the GHS to the evaluation of system performance, through environmental audits. Finally, the proposal has been socially designed with the workers of the plant, the operations and the administration, in order to consider its implementation.